Response and outcomes after anti-CTLA4 versus anti-PD1 combined with stereotactic body radiation therapy for metastatic non-small cell lung cancer: retrospective analysis of two single-institution prospective trials. Issue 1 (28th January 2020) - Chen, Dawei; Menon, Hari; Verma, Vivek; Guo, Chunxiao; Ramapriyan, Rishab; Barsoumian, Hampartsoum; Younes, Ahmed; Hu, Yun; Wasley, Mark; Cortez, Maria Angelica; Welsh, James
Abstract : Background: This study compared response rates and outcomes of combined radiotherapy and immunotherapy (iRT) based on the type of checkpoint inhibitor (anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA4) vs antiprogrammed death-1 (PD1)) for metastatic non-small cell lung cancer (mNSCLC). Methods: We retrospectively reviewed two prospective trials of radiation combined with anti-CTLA4 or anti-PD1 for patients with mNSCLC. Patients undergoing non-salvage stereotactic body radiation therapy (SBRT) to lung sites were selected from both trials and grouped by the immunotherapeutic compound received. Endpoints included in-field and out-of-field response rates, and overall response rate (complete or partial response) (all by response evaluation criteria in solid tumors). Progression-free survival (PFS) and overall survival (OS) were estimated with the Kaplan-Meier method. Results: Median follow-up times for the 33 patients (n=17 SBRT+anti-CTLA4, n=16 SBRT+anti-PD1) were 19.6 and 19.9 months. Response rates for out-of-field lesions were similar between anti-PD1 (37%) and anti-CTLA4 (24%) (p=0.054). However, global response rates for all lesions were 24% anti-CTLA4 vs 56% anti-PD1 (p=0.194). The PFS was 76% for anti-CTLA4 vs 94% anti-PD1 at 3 months, 52% vs 87% at 6 months, 31% vs 80% at 12 months, and 23% vs 63% at 18 months (p=0.02). Respective OS values were 76% vs 87% at 6 months, 47% vs 80% at 12 months, and 39% vs 66% at 18 months (p=0.08). Conclusions: Both anti-CTLA4 and anti-PD1 agents prompt a similar degree of in-field and out-of-field responses after iRT, although the global response rate and PFS were statistically higher in the anti-PD1 cohort. Further dedicated study and biological mechanistic assessment is required. Trial registration numbers: NCT02239900 and NCT02444741 .